Online adaptive radiotherapy in stereotactic body radiotherapy for pancreatic cancer patients - Dazhen Jiang; Jin Peng; Hui Xu; Dajiang Wang; Conghua Xie; Xiaoyong Wang; Fuxiang Zhou; Hui Liu (Scientific Reports)
Abstract Stereotactic radiation therapy (SBRT) has emerged as a promising treatment modality for locally advanced pancreatic cancer. The aim of this study is to assess the dosimetric efficacy of online adaptive radiotherapy (ART) in comparison to image-guided radiation therapy (IGRT) for pancreatic cancer. We conducted a retrospective analysis involving 8 patients diagnosed with locally advanced pancreatic cancer. The gross tumor volume (GTV) delineates the visible extent of the tumor on imaging, while the planning tumor volume (PTV) was generated by expanding 5 mm from the GTV and ensuring a 3 mm distance from the small intestine, duodenum, and stomach simultaneously. Treatment planning was executed using the United Imaging Healthcare Treatment Planning System workstation. The control group underwent evaluation based on daily validated fan-beam CT (FBCT) scans, assessing both the dose delivered to actual organs at risk (OARs) and the target volume. Radiotherapy plans were developed utilizing simulation CT, and conventional radiotherapy with daily image-guided radiation therapy (IGRT) was administered using FBCT-Linac. Conversely, patients in the study group received daily validated FBCT-guided adaptive radiotherapy plans, with a focus on mean dose assessment of both the target volume and OARs. Subsequently, we compared the average outcomes of each treatment fraction between IGRT and online adaptive radiotherapy (ART). Comparison between ART and IGRT treatment plans revealed significant differences in various dosimetric parameters: For PTV: V98%: ART (96.28%) vs IGRT (89.73%), p = 0.000, V95%: ART (96.28%) vs IGRT (89.73%), p = 0.031, V90%: ART (98.58%) vs IGRT (93.65%), p = 0.000, Dmean: ART (4912.91) vs IGRT (4804.11), p = 0.000. For GTV: V100%: ART (97.96%) vs IGRT (94.85%), p = 0.314, V98%: ART (100.00%) vs IGRT (96.83%), p = 0.000, V90%: ART (100.00%) vs IGRT (97.75%), p = 0.000, Dmean: ART (4972.17) vs IGRT (4907.23), p = 0.000. For the duodenum: D0.5cc: ART (2883.92) vs IGRT (3359.35), p = 0.000, D1cc: ART (2726.32) vs IGRT (3128.66), p = 0.001, D5cc: ART (2051.96) vs IGRT (2273.93), p = 0.015, D10cc: ART (1650.73) vs IGRT (1731.74), p = 0.211. For the small bowel: D0.5cc: ART (3022.3) vs IGRT (3142.64), p = 0.037. D5cc: ART (2151.09) vs IGRT (2389.15), p = 0.043, D10cc: ART (1775.20) vs IGRT (1942.00), p = 0.079. For the stomach: D0.5cc: ART (3353.92) vs IGRT (4117.85), p = 0.000, D5cc: ART (2860.20) vs IGRT (3235.41), p = 0.000, D10cc: ART (2553.72) vs IGRT (2836.73), p = 0.000. For the Dmean of the left kidney and right kidney: Left kidney: ART (248.28) vs IGRT (239.65), p = 0.100. Right kidney: ART (314.55) vs IGRT (307.17), p = 0.345. These results suggest significant improvements in PTV coverage and sparing of OARs with ART compared to IGRT, indicating the potential of ART in optimizing treatment outcomes for pancreatic cancer patients. Compared to conventional IGRT-guided SBRT programs, ART-based SBRT for pancreatic cancer not only enhances the dose distribution to the target volume but also mitigates the radiation exposure to critical organs-at-risk (OARs) such as the duodenum, small intestine, and stomach. This approach may offer a more favorable safety profile while concurrently enhancing treatment efficacy.